Fostering an Entrepreneurial Spirit Through Islamic Career Guidance Services Based on Noble Purpose (KONSELING RELIGI Jurnal Bimbingan Konseling Islam, 2022)
Islamic career guidance for students is an effort to provide assistance in preparing for the world of work, choosing jobs or certain professional positions with Islamic principles. The urgency of career guidance for students is motivated by the number of students who became unemployed after they graduated from college because they were still oriented to the ideals to find jobs, not to create jobs or entrepreneurship. Noble purpose or noble ideals in entrepreneurship will not only move students awareness to benefit themselves, but beyond the target to be able to spur on a greater benefit for many people and the surrounding environment. The purpose of this study is to find out how the implementation of Islamic career guidance in fostering the spirit of entrepreneurial spirit among students. This type of research is a field research with qualitative analysis with data collection techniques using observations, interviews and documentation. The results of this study indicate : First, the process of Islamic career guidance services is carried out comprehensively ranging from strengthening to ethics and work ethic. Second, the impact of Islamic career guidance services using noble purpose fosters spiritual values in students in entrepreneurs itself but also for others in the form of creating jobs and initiating the people around them in order to get a better life expectancy.